Sustainable Marketing: Electric Vehicles’ Commitment to a Sustainable Future - Kurian, Anita (Ushus Journal of Business Management, 2023)
The adoption of electric vehicles (EVs) in India is seen as a crucial step towards a sustainable future. As the world moves towards a more sustainable future, EVs have emerged as a promising alternative to traditional gas-powered vehicles. Sustainable marketing emphasizes the importance of social, environmental, and ethical considerations in business practices. Companies that produce and market EVs can use sustainable marketing tactics to showcase their commitment to a sustainable future and appeal to consumers who prioritize responsible choices. This includes promoting the environmental and economic benefits of EVs, using eco-friendly materials in production and packaging, and partnering with organizations that promote sustainable practices and causes. By exploring the intersection of sustainable marketing and EVs, this research paper aims to contribute to a better understanding of how businesses can drive sustainability and promote responsible consumer behaviour. The purpose of this conceptual paper is to identify the sustainability factors that drive countries to promote EVs. To conclude, this paper examined articles published after 2015. The researcher examined various papers to better understand the true sustainability threat posed by EVs.